Atrial natriuretic factor receptor guanylate cyclase, ANF-RGC, transduces two independent signals, ANF and Ca2+ - Duda, Teresa; Pertzev, Alexandre; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2014)
Atrial natriuretic factor receptor guanylate cyclase, ANF-RGC, was the first discovered member of the mammalian membrane guanylate cyclase family. The hallmark feature of the family is that a single protein contains both the site for recognition of the regulatory signal and the ability to transduce it into the production of the second messenger, cyclic GMP. For over two decades, the family has been classified into two subfamilies, the hormone receptor subfamily with ANF-RGC being its paramount member, and the Ca2+ modulated subfamily, which includes the rod outer segment guanylate cyclases, ROS-GC1 and 2, and the olfactory neuroepithelial guanylate cyclase, ONE-GC. ANF-RGC is the receptor and the signal transducer of the most hypotensive hormones, atrial natriuretic factor (ANF) and B-type natriuretic peptide (BNP). After binding these hormones at the extracellular domain it, at its intracellular domain, signals activation of the C-terminal catalytic module and accelerates the production of cyclic GMP. Cyclic GMP then serves the second messenger role in biological responses of ANF and BNP such as natriuresis, diuresis, vasorelaxation and anti-proliferation. Very recently another modus operandi for ANF-RGC was revealed. Its crux is that ANF-RGC activity is also regulated by Ca2+. The Ca2+ sensor neurocalcin  mediates this signaling mechanism. Strikingly, the Ca2+ and ANF signaling mechanisms employ separate structural motifs of ANF-RGC in modulating its core catalytic domain in accelerating the production of cyclic GMP. In this review the biochemistry and physiology of these mechanisms with emphasis on cardiovascular regulation will be discussed.